55 Determination of local interventional reference levels in heart surgery using a dose archiving and communication system. (December 2018) - Sarcy, S.; LePrince, P.; Jenny, C.; Maisonobe, J.-A.
Abstract : Introduction: In cardiology, exposure of patients to ionizing radiations can reach significant levels and may sometimes cause serious complications. By taking advantage of the connection of a cardiac surgery room to the DACS ( Dose Archiving and Communication System), we are seeking to determine the Local Interventional Reference Levels (IRLs) for procedures performed in this room. Methods: The heart surgery department of the Pitié-Salpêtrière hospital has a fixed installation (Allura Xper FD20, Philips) connected to the institutional DACS, RDM (Radiation Dose Monitor, Medsquare) since June 2016. This retrospective study examines the files recorded in the DACS of all the patients that underwent a surgery using this installation from June 2016 to December 2017. For all the files considered, the procedure indicated in the DACS is reassigned as a function of the act performed. Three main groups were defined: ECMO (ExtraCorporeal Membrane Oxygenation), Endoprosthesis and TAVI (Transcatheter Aortic Valvular Implantation). Acts such as aortic dilatation, pacemaker insertion or angioplasty, less frequent in this room, are clustered in "Other acts". Patients for whom the procedures are not known are gathered in a last group: NA. For the 3 main groups, medians, 75th percentiles (local IRLs), means, standard deviation, minimum and maximum values for the Dose Area Product (DAP, in mGy.cm 2 ), the air kerma (Kair, in mGy) at the interventional reference point and the fluoroscopy time (min) are extracted using the DACS. Results: A total of 430 files are recorded in the DACS: 16 in ECMO, 16 in Endoprosthesis, 275 in TAVI, 37 in Other Acts, 80 in NA. 6 files are excluded for recording reasons. For the ECMO, Endoprosthesis and TAVI groups, local IRLs of Kair are 120, 999 and 762 mGy, respectively. For DAP, the local IRLs are 46, 867, 233, 923 and 146, 539 mGy.cm 2, respectively. All the extracted values are shown in Table 1. Conclusions: Once each of the surgical acts has been reassigned to a given procedure, the use of the DACS allows us to determine, quickly and globally, local IRLs for each procedure performed in this room. However, the reassignment of retrospective acts for this study is time-consuming: a priori assignment will be considered in the remainder of this work. The small number of files for ECMO and Endoprosthesis groups limits robustness of IRLs proposed for these acts. These acts being infrequent in this room, we will seek to expand the data to include a minimum of 30 files. On the other hand, for the TAVI group, the values obtained will be set as local IRLs in the DACS.